2019
DOI: 10.1094/pdis-02-19-0401-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Powdery Mildew Resistance Gene pmDHT at or Closely Linked to the Pm5 Locus in the Chinese Wheat Landrace Dahongtou

Abstract: Chinese wheat landrace Dahongtou was resistant to 35 of 38 tested Chinese isolates of Blumeria graminis f. sp. tritici at the seedling stage. Genetic analysis of the F2 populations and their derived F2:3 families of crosses of Dahongtou with the susceptible varieties Mingxian 169 and Huixianhong indicated that the resistance of Dahongtou to B. graminis f. sp. tritici isolate E09 was conferred by a single recessive gene, tentatively designated as pmDHT. The gene was mapped to chromosome arm 7BL and flanked by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 65 publications
0
16
0
2
Order By: Relevance
“… BAF is the frequency of the advantageous alleles within the PGR population (n = 7,510) and the elite population (Elite, n = 170). Sources: (4) Hsam et al, 1998 , (5) Hsam et al, 2001 , (6) Hsam et al, 2003 , (11) Law and Wolfe, 1966 , (12) Huang et al, 2003 , (13) Huang et al, 2000 , (14) Marone et al, 2013 , (16) Friebe et al, 1994 , (18) Tosa et al, 1988 , (19) Tosa and Sakai, 1990 , (22) Hao et al, 2015 , (26) Järve et al, 2000 , (27) Peusha et al, 2000 , (29) Liu et al, 2002 , (34) Blanco et al, 2008 , (36) Lillemo et al, 2008 , (38) Luo et al, 2009 , (45) Xiao et al, 2013 , (50) Jia et al, 1996 , (69) Xu et al, 2018 , (70) Qie et al, 2019 , (83) Li H. et al, 2020 , (82) XU et al, 2018 , (83) Li H. et al, 2020 , (85) Fu et al, 2017 , (86) Jin et al, 2020 . …”
Section: Resultsmentioning
confidence: 99%
“… BAF is the frequency of the advantageous alleles within the PGR population (n = 7,510) and the elite population (Elite, n = 170). Sources: (4) Hsam et al, 1998 , (5) Hsam et al, 2001 , (6) Hsam et al, 2003 , (11) Law and Wolfe, 1966 , (12) Huang et al, 2003 , (13) Huang et al, 2000 , (14) Marone et al, 2013 , (16) Friebe et al, 1994 , (18) Tosa et al, 1988 , (19) Tosa and Sakai, 1990 , (22) Hao et al, 2015 , (26) Järve et al, 2000 , (27) Peusha et al, 2000 , (29) Liu et al, 2002 , (34) Blanco et al, 2008 , (36) Lillemo et al, 2008 , (38) Luo et al, 2009 , (45) Xiao et al, 2013 , (50) Jia et al, 1996 , (69) Xu et al, 2018 , (70) Qie et al, 2019 , (83) Li H. et al, 2020 , (82) XU et al, 2018 , (83) Li H. et al, 2020 , (85) Fu et al, 2017 , (86) Jin et al, 2020 . …”
Section: Resultsmentioning
confidence: 99%
“…Seedling stage reactions of YT2 to 22 single-pustule-derived isolates were separately assessed with three replicates at the greenhouse as described ( Qie et al, 2019 ). These isolates were collected from different wheat production regions of China and were characterized by their individual identifying host ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Pm5e was initially detected in Fuzhuang 30, a cultivar selected from Jinghui 30 that was developed from a cross between two Chinese wheat landraces Liquanheshangtou and Huaxianqisifeng in Shaanxi Province in the 1940s ( Huang et al, 2003 ). Subsequent studies identified several genes allelic to Pm5e in wheat landraces, e.g., Hongquanmang ( PmH ) ( Zhou et al, 2005 ), Hongyoumai ( pmHYM ) ( Fu et al, 2017 ), Baiyouyantiao ( PmBYYT ) ( Xu et al, 2018a ), Shangeda ( PmSGD ) ( Xu et al, 2018b ), Dahongtou ( pmDHT ) ( Qie et al, 2019 ), Youbailan ( pmYBL ) ( Xu et al, 2020 ), Xiaobaidong ( mlxbd ) ( Xue et al, 2009 ), and Duanganmang ( PmDGM ) ( Wu et al, 2021 ). Most of these landraces were ever grown in the Guanzhong Plain, Shaanxi Province, or nearby regions ( Xie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%